Veljavnost in zanesljivost Lestvice akademske motivacije na vzorcu slovenskih študentov - Puklek Levpušček, Melita (Psihološka obzorja (Ljubljana), 2017)
In this study we examined construct validity and reliability of the Academic Motivation Scale, College Version (Academic Motivation Scale, AMS-C 28, Vallerand et al., 1992) and its relationship with gender, certainty of study choice and career goals in Slovenian university students. The theoretical basis of AMS is derived from Self-Determination Theory, which identified different types of motivation on a continuum from amotivation to different types of external motivation and intrinsic (self-determined) motivation. The AMS measures multidimensional motivational construct and contains seven scales. The validation sample consisted of 324 students of various studies at the University of Ljubljana. Multigroup confirmatory factor analysis showed an acceptable fit of the original 7-factor structure on Slovenian data and measurement invariance across gender. The highest were correlations among the three factors of intrinsic motivation and among the three factors of external motivation. Current certainty of study choice was positively associated with all three factors of intrinsic motivation and identified regulation, and negatively correlated with amotivation. Extrinsic career goals had low to moderate positive correlations with factors of external motivation while intrinsic career goals correlated positively with the three factors of intrinsic motivation, identified and introjected regulation, and negatively with amotivation. Female students had higher scores on intrinsic motivation to accomplish, and identified and introjected regul ation than male students. In sum, the AMS C-28 showed good construct and convergent validity and reliability in Slovenian university context.
Keywords: sestava testa; vprašalniki; motivacija za študij; poklicni cilji; student; študenti; Lestvice akademske motivacije AMS-C 28; Lestvica poklicnih ciljev CGS